2006
DOI: 10.1097/01.mib.0000228998.29466.ac
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors in inflammatory bowel disease: A co-twin control study of a Swedish-Danish twin population

Abstract: The observed associations indicate that markers of possible infectious events may influence the risk of IBD. Some of these effects might be mediated by long-term changes in gut flora or alterations in reactivity to the flora. The influence of smoking in IBD was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 154 publications
(134 citation statements)
references
References 48 publications
2
128
2
2
Order By: Relevance
“…Finally, the Oxford Family Planning Association contraceptive study showed that the risk of developing CD in women was more than threefold higher in smokers than nonsmokers ( 168 ). In twin studies, Bridger found that in 23 dichotomous twin pairs, the smoker twin had CD in 91% of cases with an OR of 10.5 (95% CI, 2.6-92) and in another more recent study, the smoking twin from discordant pairs demonstrated an OR of 2.9 (95% CI, 1.2-7.1) ( 169 ). A meta-analysis by Mahid et al examined a total of nine studies reporting on smoking and development of CD ( 170 ).…”
Section: Summary Of Evidencementioning
confidence: 96%
“…Finally, the Oxford Family Planning Association contraceptive study showed that the risk of developing CD in women was more than threefold higher in smokers than nonsmokers ( 168 ). In twin studies, Bridger found that in 23 dichotomous twin pairs, the smoker twin had CD in 91% of cases with an OR of 10.5 (95% CI, 2.6-92) and in another more recent study, the smoking twin from discordant pairs demonstrated an OR of 2.9 (95% CI, 1.2-7.1) ( 169 ). A meta-analysis by Mahid et al examined a total of nine studies reporting on smoking and development of CD ( 170 ).…”
Section: Summary Of Evidencementioning
confidence: 96%
“…The genetic influence is also supported by higher concordance rates (approximately 50%) for CD occurrence in monozygotic twins (Tysk et al, 1988;Orholm et al, 2000;Halfvarson et al, 2003;Jess et al, 2005). Still, approximately 50% of identical twin pairs are discordant for CD (that is, one is diseased and one is healthy) demonstrating that environmental factors are also important for disease incidence (Loftus, 2004;Halfvarson et al, 2006).…”
Section: Introductionmentioning
confidence: 71%
“…Similar observations have been made in IBD where siblings that were smokers tended to develop CD while non-smokers developed UC. [25,26] In CD, women are more affected by smoking and they have a higher relative risk, sometimes as much as three-fold [27].…”
Section: Discussionmentioning
confidence: 99%